Safety of totally implantable venous access devices and peripherally inserted central catheters in hematological malignancies patients: a meta-analysis - Gu, Meier; Huang, Xiaguang (Frontiers in Oncology, 2025)
BackgroundThe use of totally implantable venous access devices (TIVADs) and peripherally inserted central catheters (PICCs) are the two options for patients receiving chemotherapy for hematologic malignancies. However, it remains unclear which approach yields superior patient outcomes. This meta-analysis aimed to compare the efficacy of TIVAPs and PICCs in patients undergoing chemotherapy for hematologic malignancies.MethodsA comprehensive literature search was conducted in PubMed, Embase, Cochrane Library, Wanfang, and China National Knowledge Infrastructure (CNKI) to identify available articles comparing the effect of TIVADs and PICCs. Statistical analyses were performed using RevMan 5.3 and STATA 12.0, with odds ratios (OR) and 95% confidence intervals (CI) used as effect indicators.ResultsA total of 10 studies, including 784 patients (386 in the TIVAD group and 398 in the PICC group), met the eligibility criteria. The meta-analysis results demonstrated that compared with PICCs, TIVAPs were associated with lower significantly risks of infection (OR: 0.21, 95% CI: 0.11-0.40), catheter occlusion (OR: 0.31, 95% CI: 0.13-0.77), phlebitis (OR: 0.16, 95% CI: 0.06-0.42), and catheter dislodgement (OR: 0.25, 95% CI: 0.08-0.76) compared to PICCs. However, there was no significant difference between the two devices in terms of thrombosis risk (OR: 0.37, 95% CI: 0.10-1.41).ConclusionThis meta-analysis suggests a potential association between TIVAPs and a lower risk of complications compared with PICCs in patients with hematologic malignancies undergoing chemotherapy.